Effect of decreased suspended sediment content on chlorophyll-a in Dongting Lake, China - Zhang, Le; Lou, Yu; Mei, Jinhua; Wu, Haipeng; Xia, Le; Dai, Juan; Dai, Yuping; Xu, Guxiang; Yu, Yuantao; Wang, Jiehui (Frontiers in Ecology and Evolution, 2025)
Global damming of rivers strongly impacts the transport and characteristic of sediment, resulting in a significant reduction in the suspended sediment content (SSC) flowing into the downstream. The reduction in SSC may influence chlorophyll-a (Chl-a) concentrations in water, thereby further affecting the aquatic ecological environment. However, the effect of reduced SSC on Chl-a is poorly studied. Here, we compared and analyzed the distribution conditions of Chl-a in 6 representative years for both before the implementation of Three Gorges Dam (TGD) (BIT) and after the implementation of TGD (AIT), using the TM/OLI data and NIR-red inversion model. The findings showed that, from BIT to AIT, the area proportion of ultraoligotrophic state significantly decreased, while the area proportion of oligotrophic, mesotrophic, and eutrophic states significantly increased, with eutrophic state observed for the first time in 2017. Additionally, a significant correlation between Chl-a concentration and SSC was found. The area proportion of ultraoligotrophic state was positively correlated with SSC, while oligotrophic and mesotrophic states were negatively correlated with SSC. The reduction in SSC enhanced water promoting phytoplankton growth and consequently increasing Chl-a concentrations. This study highlights the spatiotemporal variations of Chl-a dynamics in DL before and after the operation of the TGD and discusses the impacts of SSC on water trophic states and the ecosystem. The findings provide valuable scientific insights for large-scale lake water quality monitoring and offer critical reference points for future water quality management strategies.